Reduction of potentially inappropriate medication in the elderly: design of a cluster-randomised controlled trial in German primary care practices (RIME) - Ulrich Thiem; Stefan Wilm; Wolfgang Greiner; Henrik Rudolf; Hans-Joachim Trampisch; Christiane Müller; Gudrun Theile; Petra A. Thürmann (SAGE Publishing, 2020)
Background: Potentially inappropriate medication (PIM) is considered to have potentially more harmful than beneficial health effects in elderly patients. A German example for a PIM list is the PRISCUS list that has been available since 2010. PIMs are associated with an increased risk of hospitalisation and adverse health outcomes. Furthermore, drug-drug interactions (DDI) may pose additional risks to patients. It is not yet clear how numbers of PIM and DDI can be reduced in community-dwelling seniors in primary care; nor is it clear whether patients would benefit from such deprescribing. Methods: The cluster-randomised controlled study on the "Reduction of potentially Inappropriate Medication in the Elderly" (RIME study) is designed to examine whether an intervention based on the PRISCUS list can lower the proportion of community-dwelling people of ⩾70 years taking at least one PIM and/or medication inducing at least one dangerous DDI. The intervention consists of professional education and training on the reduction of PIM and DDI, and will be offered to either general practitioners (GPs) alone or GPs and their office staff in the experimental study arm. The control group will be offered professional education and training on more general issues of prescribing in the elderly, not specifically addressing PIM or DDI. The primary endpoint is the difference in the proportion of patients with at least one PIM or DDI between the start of the study and study closure after 12 months as compared between intervention and control group. Secondary endpoints include overall mortality, number of hospitalisations during the course of the study, quality of life and costs. Secondary analyses will be explorative, with the cluster randomisation being factored in. Discussion: The RIME study will contribute to answering the question of whether an intervention based on the PRISCUS list can reduce the proportion of community-dwelling seniors aged ⩾70 years with at least one PIM and/or DDI, and whether this will result in positive health effects, for example, as regards hospitalisations. Trial registration The Study has been registered in the German Clinical Trials Register (DRKS) under the number DRKS00003610. Lay summary Reduction of potentially inappropriate medication in the elderly Improper medication is a common problem in elderly with chronic diseases, and especially those with multiple diseases. Improper medication is assumed to cause side effects, reduced quality of life, more hospital admissions and other negative consequences. Improper medication may by avoided by lists like the German PRISCUS list published in 2010. The list contains drugs that are assumed to be improper in the opinion of experts. The list also gives hints how drugs may interact, and how drugs should be dosed appropriately. A training of general practitioners based on such a list may reduce improper medication. To evaluate this, a scientific project is planned and conducted. In a total of 140 general practitioner offices in the cities of Witten and Hannover, 12 patients in each office aged ⩾70 years and taking at least 6 drugs on a regular basis will be examined. The treating physicians will either get usual recommendations towards pharmacotherapy in the elderly, or they will be advised and trained in new developed recommendations based on the PRISCUS list. After 12 months, the proportion of patients receiving at least one improper medication will be assessed, and the proportions will be compared between the differently trained physician groups. It is assumed that one in four patients will get at least one improper medication, and that the new developed recommendations will reduce the proportion of patients with improper medication by a third.